PEMBELAJARAN BAHASA ARAB DI MADRASAH IBTIDAIYAH (TINJAUAN PADA KOMPETENSI GURU DAN MODEL PEMBELAJARAN) - Susiawati, Iis; Zulkarnain, Zulkarnain; Safitri, Wiena; Mardani, Dadan (El-Tsaqafah : Jurnal Jurusan PBA, 2022)
This study aims to show that the competence of Arabic language teachers in choosing the right learning model can determine the success of the planned Arabic learning objectives. In this case, Arabic teachers need to continue to develop their competencies, which include language competence, cultural competence and communicative competence. The subjects of this study were Arabic teachers and grade 5 and 6 students of Madrasah Ibtidaiyah Al-Zaytun Gantar Indramayu. This study uses a qualitative descriptive approach and method. Data was collected by observation, interviews and documentation. The results of the study indicate that the competence of Arabic language teachers in Madrasah Ibtidaiyah still needs to be developed with various education and training programs for Arabic teachers to be able to improve the quality of Arabic learning based on adequate Arabic teacher competencies.